МОДЕЛЬ ЗАВАД В КОНТУРІ НУЛЬОВОЇ ПОСЛІДОВНОСТІ РОЗПОДІЛЬНОЇ МЕРЕЖІ З НЕЗАЗЕМЛЕНОЮ НЕЙТРАЛЛЮ - Лисенко, В.А. (Інститут електродинаміки НАН України, Київ, 2012)
The reasons of appearing signals in the zero-sequence electric circuit with ungrounded neutral are presented. The literatures containing information about possible sources of noise, which can get into the circuit zero-sequence are analyzed. The results of experiment in the real distribution electrical networks are presented. The parameters of noise, which are measured, are analyzed. The mathematical model of noise is offered. The principles of automation and single-phase earth fault protection that eliminate or reduce the impact of noise are proposed. References 4.